Teaching science and mathematics in English: does it violate article 152 of the federal constitution? / Ili Najwa Abdul Jalil, Nurul Izzaty Ismail and Suhaidzan Zahari - Abdul Jalil, Ili Najwa; Ismail, Nurul Izzaty; Zahari, Suhaidzan (2009)
The policy of teaching Science and Mathematics in English, which was introduced in 2003 to change the medium of teaching these subjects from Bahasa Melayu to English. The main objectives, is that to prepare the students face the globalization era where the medium of communication and the materials involving these two subjects are mainly in English. However, there were certain group of people who were doubt about the validity of this policy because it is somehow seems to be violating Article 152 of the Federal Constitution. Other than that, they also claimed this policy might deprive our national language, which is the Malay language. Furthermore, we also refer to other acts in sequence for us to understand in details about this policy's background from the constitutional point of view. The other two acts were National Language Act 1963/67 and also Education Act 1966. Our research is focusing on the issue of whether it really violates the law and Article 152 of the Federal Constitutions. Besides that, this research was done in order for us to clarify the validity of this policy and also the needs of implementing this policy in the national education system. This research was done sequentially to clarify the legal issue brought up by individuals as well as to help the public to understand the legal position of using English as a medium of communication especially in the schools. It is aimed to discover a better method to make sure this policy is effective and remained as one of the Government policy.